Cardiovascular Effects of Transcranial Direct Current Stimulation and Bimanual Training in Children With Cerebral Palsy. Issue 1 (January 2021) - Keller-Ross, Manda L.; Chantigian, Daniel P.; Nemanich, Samuel; Gillick, Bernadette T.
Abstract : Purpose: To determine the influence of combined transcranial direct current stimulation (tDCS) to the motor cortex (M1) and bimanual training on cardiovascular function in children with cerebral palsy (CP). Methods: Mean arterial pressure (MAP), heart rate (HR), and HR variability (HRV) were measured immediately before and after 20 minutes of cathodal tDCS to contralesional M1 and bimanual training on days 1, 6, and 10 of a 10-day trial in 8 participants (5 females, 7-19 years). Results: Baseline MAP and HR were similar across days (93 ± 10 mm Hg and 90 ± 10 bpm, P > .05). MAP was similar from baseline to postintervention across all 3 days. Systolic pressure, diastolic pressure, nor HR significantly changed. HRV was not influenced by the 10-day intervention. Conclusions: Combined cathodal tDCS to M1 and bimanual training does not influence autonomic and cardiovascular function in children with CP due to perinatal stroke. Abstract : Supplemental Digital Content is Available in the Text.This study investigated the influence of combined transcranial direct current stimulation to the motor cortex and bimanual training on cardiovascular function in children with cerebral palsy.